STRUCTURAL RELIABILITY OF AIR TRAFFIC CONTROLLERS - Kozhokhina, Olena; Gribov, Victor; Rudas, Sergiy (Proceedings of National Aviation University (archive), 2014)
The types of air navigation systems operator’s reliability based on the causes of errors are considered.The structural-analytical model of air navigation systems operator’s reliability is developed. The mathematicaldependence for calculation of the probability of error-free operation of air navigation systems operator is determined.